Region-based super-resolution aided facial feature extraction from low-resolution video sequences - Çelik, Turgay; Direko?lu, Cem; Özkaramanli, H.; Demirel, Hasan; Uyguro?lu, Mustafa K. (My University, 2005)
Facial feature extraction is a fundamental problem in image processing. Correct extraction of features is essential for the success of many applications. Typical feature extraction algorithms fail for low resolution images which do not contain sufficient facial detail. In this paper, a region-based super-resolution aided facial feature extraction method for low resolution video sequences is described. The region based approach makes use of segmented faces as the region of interest whereby a significant reduction in computational burden of the super-resolution algorithm is achieved. The results indicate that the region-based super-resolution aided extraction algorithm provides significant performance improvement in terms of correct detection in accurately locating the facial feature points. © 2005 IEEE.
2005 IEEE International Conference on Acoustics, Speech, and Signal Processing, ICASSP '05 --
Keywords: Facial feature extraction; Feature extraction algorithms; Low resolution images; Super resolution; Algorithms; Computational complexity; Feature extraction; Image analysis; Object recognition; Optical resolving power; Video signal processing; Face recognition